The Effect Organizational Structure and Work Motivation On Vendor’s Employee performance at Automotive Distributor in Indonesia - Oloan Situmorang; Mukhneri Mukhtar; Mahmuddin Yasin (Journal of Business and Behavioural Entrepreneurship, 2020)
Abstract. This study aim to determine and analyze the effect of organizational structure and work motivation on the employe performance at Automotive Distributor in Indonesia. This study use quantitative research method with survey technique to respond the test hypotheses that have been formulated. The respondents are 100 employe, the sampling technique used was sampling random technique. The questionaire of organizational structure and work motivation and employe performance were validated with the product moment correlation formula, while reliability was measured by the Alpha Cronbach formula. Tested of the hypothesis in this study use of the path analysis. The research result of the study found that: (1) The organizational structure of the positive direct effect on employe performance (2) The work motivation of the positive direct effect on employe performance and (3) The organizational structure of the positive direct effect toward the work motivation. The results of the study show that in the effort to improve the employe performance can be done trough of the effective of organizational structure must be increased and the improve of work motivation.